3D-QSAR-aided design, synthesis, in vitro and in vivo evaluation of dipeptidyl boronic acid proteasome inhibitors and mechanism studies. Issue 11 (1st June 2016) - Lei, Meng; Feng, Huayun; Wang, Cheng; Li, Hailing; Shi, Jingmiao; Wang, Jia; Liu, Zhaogang; Chen, Shanshan; Hu, Shihe; Zhu, Yongqiang
Graphical abstract: Abstract: Proteasome had been clinically validated as an effective target for the treatment of cancers. Up to now, many structurally diverse proteasome inhibitors were discovered. And two of them were launched to treat multiple myeloma (MM) and mantle cell lymphoma (MCL). Based on our previous biological results of dipeptidyl boronic acid proteasome inhibitors, robust 3D-QSAR models were developed and structure–activity relationship (SAR) was summarized. Several structurally novel compounds were designed based on the theoretical models and finally synthesized. Biological results showed that compound12e was as active as the standard bortezomib in enzymatic and cellular activities. In vivo pharmacokinetic profiles suggested compound12e showed a long half-life, which indicated that it could be administered intravenously. Cell cycle analysis indicated that compound12e inhibited cell cycle progression at the G2M stage.